Vitamin D and health - The missing vitamin in humans - Szu-Wen Chang; Hung-Chang Lee (Elsevier, 2019)
Severe vitamin D deficiency may cause rickets in infants or children and osteomalacia in adults, though it is now uncommon in developed countries. However, subclinical vitamin D deficiency is more prevalent, and it is associated with osteoporosis and higher incidence of falls or fractures. It was reported that 96% children with rickets were breastfed, since breast milk contains inadequate vitamin D. The American Academy of Pediatrics 2008 recommended infants who were exclusively or partially breastfed required 400 international units vitamin D daily from the first few days of life. Furthermore, since vitamin D receptors are present all over the body, insufficient vitamin D status may correlate with several extra-skeletal effects, such as pregnancy-related complications and immune dysfunction. This paper discusses the researches regarding system-based vitamin D effects, the possible risk factors leading to vitamin D deficiency, and the recommendations of vitamin D requirements. It is well-known that vitamin D can be obtained by sun exposure or limited natural dietary sources. The American Academy of Dermatology declared ultraviolet radiation to be a known skin carcinogen, so it may not be safe or efficient to obtain vitamin D via sun exposure or other artificial sources. Therefore, many pediatricians and physicians recommend appropriate vitamin D supplementation to achieve optimal plasma concentration. Trials assessing the effects of vitamin D repletion and establishing its optimum serum level are ongoing. Medical advice for vitamin D supplementation should be individualized accordingly. Key Words: deficiency, insufficiency, supplementation, vitamin D